The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1073/pnas.1013048107
|View full text |Cite
|
Sign up to set email alerts
|

Differential correction of lagging-strand replication errors made by DNA polymerases α and δ

Abstract: Mismatch repair (MMR) of replication errors requires DNA ends that can direct repair to the newly synthesized strand containing the error. For all but those organisms that use adenine methylation to generate nicks, the source of these ends in vivo is unknown. One possibility is that MMR may have a "special relation to the replication complex" [Wagner R, Jr., Meselson M (1976) Proc Natl Acad Sci USA 73: [4135][4136][4137][4138][4139], perhaps one that allows 5′ or 3′ DNA ends associated with replication to act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 46 publications
4
82
0
Order By: Relevance
“…Evidence in support of this hypothesis came from in vivo studies in S. cerevisiae showing that the lagging strand was more efficiently repaired by MMR (Pavlov et al 2003;Nick McElhinny et al 2010) possibly due to the ready availability of DNA termini where MMR could initiate. The hypothesis could also be substantiated by in vitro studies using extracts of human cells and circular substrates carrying single mismatches.…”
Section: Degradation Of the Error-containing Strandmentioning
confidence: 75%
“…Evidence in support of this hypothesis came from in vivo studies in S. cerevisiae showing that the lagging strand was more efficiently repaired by MMR (Pavlov et al 2003;Nick McElhinny et al 2010) possibly due to the ready availability of DNA termini where MMR could initiate. The hypothesis could also be substantiated by in vitro studies using extracts of human cells and circular substrates carrying single mismatches.…”
Section: Degradation Of the Error-containing Strandmentioning
confidence: 75%
“…Thus, the absence of a proofreading activity in Pol a requires that errors made by it are corrected by other mechanisms. For instance Pol d, but not Pol 1, proofreads errors made by Pol a, in addition to error correction by the mismatch repair system (Pavlov et al 2006;Nick McElhinny et al 2010a).…”
Section: Eukaryamentioning
confidence: 99%
“…One of the first papers to describe MMR suggested that the MMR repair complex could have a special relationship with the replication apparatus (4), and that idea seems to be a central feature of strand discrimination in eukaryotes. In a study published in PNAS, Nick McElhinny et al (5) provide evidence that the close relationship between MMR and replication leads to preferential repair of mismatches near initiation sites for DNA synthesis.…”
mentioning
confidence: 99%
“…Determination of MMR correction with regard to Pol ε errors and individual measurements of MutSα and MutSβ correction activity, all of which are underway, should be especially revealing. The recent papers in PNAS (5,11) show the relationship of MMR with the replication apparatus to be critical in its strand discrimination activity. The paper by Pluciennik et al (11) is particularly important in illustrating how strand discrimination can be achieved on the leading strand, and Nick McElhinny et al (5) demonstrate that the 5′ ends of Okazaki fragments do, in fact, appear to be used for strand discrimination on the lagging strand.…”
mentioning
confidence: 99%
See 1 more Smart Citation